2022
DOI: 10.3389/fpsyg.2022.925963
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Marketing: A Systematic Literature Review and an Agenda for Future Inquiry

Abstract: Augmented reality (AR) is a potentially disruptive technology that enriches the consumer experience and transforms marketing. With the surging popularity of AR in marketing practice, academic efforts to investigate its effects on consumer experience, response, and behavior have increased significantly. To obtain an integrated and comprehensive view of the front-line in AR marketing research and identify the gaps for future research, we analyze the existing AR marketing literature through a systematic literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 107 publications
2
16
0
Order By: Relevance
“…The present study concurs with Riar et al. (2022) and Du et al. (2022) that there needs to be more research on consumers' intentions to adopt AR apps in e-retailing since the technology is still in its infancy.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study concurs with Riar et al. (2022) and Du et al. (2022) that there needs to be more research on consumers' intentions to adopt AR apps in e-retailing since the technology is still in its infancy.…”
Section: Introductionsupporting
confidence: 90%
“…Thus, this study examines how electronic retail businesses adopt AR apps. The present study concurs with Riar et al (2022) and Du et al (2022) that there needs to be more research on consumers' intentions to adopt AR apps in e-retailing since the technology is still in its infancy. The significance of the current study appears in that most previous research studies relied mainly on the technology acceptance model (TAM) model (Castillo and Bigne, 2021;Saleem et al, 2022).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The concept of AR is a significant area for new research in the marketing discipline, as shown through recent literature reviews (e.g., Du et al, 2022; Kumar et al, 2023; Rejeb et al, 2021). Broadly speaking, these studies have focused on defining AR marketing and its characteristics (Hilken et al, 2018; Javornik, 2016; Rauschnabel, Felix, et al, 2022) or assessed strategic (Hilken, Chylinski, et al, 2022; Javornik, Duffy, et al, 2021; Rauschnabel, Babin, et al, 2022) and consumer‐related (e.g., Kumar et al, 2023; Sung et al, 2021; tom Dieck & Han, 2022) research questions.…”
Section: Theory and Prior Researchmentioning
confidence: 99%
“…A multitude of SLRs relates already to the retail sector (Bonfrer et al, 2022;Cai and Lo, 2020;Lagorio and Pinto, 2021). Some research papers analyse technologies in the context of retail activities with a SLR (Du et al, 2022;Xi and Hamari, 2021;Xue et al, 2019). AI is reshaping retail (Shankar, 2018).…”
Section: Step 1: Identify the Research Problemmentioning
confidence: 99%